THE ROLE OF JOINT AUDITING IN REDUCING TAX EVASION AND INCREASING TAX REVENUES: AN APPLIED STUDY - Nuha Aadi Abd Ali; Shaymaa Abdulhusein Abdulkadhim Alisawi; Hayder Oudah Kadhim (Scholar Express Journals, 2024)
The research objectives to show the role of joint audit in reducing tax evasion and increasing tax revenue by identifying appropriate approaches that help in developing tax structure in a manner proportionate with the changes accompanying the contemporary environment, Therefore, a joint audit is a systematic procedure for gathering and objectively presenting evidence regarding management claims regarding economic events and activities in order to assess how well these assurances align with established values and provide the results to revelries involved, provided that two or more auditors conduct the process. The study sample is signified by employees of the General Tax Authority, including managers, accountants, accountants and financial analysts for fiscal year ending on 31/12/2023. The most significant of the research's findings was that taxes are important for more reasons than just the state's general revenue and that joint reviewing helps decrease tax shirking and tax evasion in a method that helps the state treasury collect financial resources to provision it so that it can apply on public services, defense, security, and education. But also due to the issues that tax studies bring up about the economy, law, society, and politics.
Keywords: Joint Auditing; Tax Evasion